Indigenous Girlhood: Narratives of Colonial Care in Law and Literature - Scribe, Megan (2020)
As Canada assumes legal responsibility over an unprecedented number of Indigenous girls entering carceral facilities, educational boarding arrangements, and foster care, it is important to examine how the state is implicated in harming these girls. While these institutions ostensibly exist to provide Indigenous girls with care, they actually place Indigenous girls at greater risk of violence, disappearance, and death. Rather than focus on children or women more broadly, this dissertation considers how Indigenous girls' unique social location and legal minor status subjects these girls to greater state surveillance and management. What’s more, this analysis establishes connections between state violence against Indigenous girls and Canada’s settler colonial regime. This dissertation is organized into two parts. In part one, I examine the production of colonial narratives about violence against Indigenous girls through the Inquiry into the Circumstances Surrounding the Death of Phoenix Sinclair (2013) and the Inquest into the Deaths of Seven First Nations Youth (2016). In part two, I shift my attention toward Indigenous feminist literature on Indigenous girlhood. Through a close reading of Tracey Lindberg’s Birdie (2015) and The Break (2016) by Katherena Vermette, this study considers the theoretical and methodological possibilities of Indigenous feminist storytelling. Through an extensive examination of legal processes and Indigenous feminist literature, this dissertation offers innovative theoretical and methodological tools for addressing settler colonialism and other structures of oppression targeting Indigenous girls, as well as paths forward. Ph.D.